Let It Die" - Arwen Spicer (b. 1975) (Dispatches from Anarres: Tales in Tribute to Ursula K. Le Guin, 2021)
The story is set in a future that severely restricts the use of technology, allowing its use solely to repair visiting spaceships and allows people in their community to die rather than using technology to create treatments for them.
Keywords: Female author; US author